Altered Biogenesis and MicroRNA Content of Hippocampal Exosomes Following Experimental Status Epilepticus - Batool, Aasia; Hill, Thomas D. M.; Nguyen, Ngoc T.; Langa, Elena; Diviney, Mairéad; Mooney, Catherine; Brennan, Gary P.; Connolly, Niamh M. C.; Sanz-Rodriguez, Amaya; Cavanagh, Brenton L.; Henshall, David C. (Frontiers in Neuroscience, 2020)
Repetitive or prolonged seizures (status epilepticus) can damage neurons within the hippocampus, trigger gliosis and generate an enduring state of hyperexcitability. Recent studies have suggested that microvesicles including exosomes are released from brain cells following stimulation and tissue injury, conveying contents between cells including microRNAs. Here, we characterised the effects of experimental status epilepticus on the expression of exosome biosynthesis components and analysed microRNA content in exosome-enriched fractions. Status epilepticus induced by unilateral intra-amygdala kainic acid in mice resulted in acute subfield-specific, bi-directional changes in hippocampal transcripts associated with exosome biosynthesis including up-regulation of ESCRT–dependent and –independent pathways. Increased expression of exosome components including Alix were detectable in samples obtained two weeks after status epilepticus and changes occurred in both the ipsilateral and contralateral hippocampus. Small RNA sequencing of exosome-enriched fractions prepared using two different techniques detected a rich diversity of conserved microRNAs and showed that status epilepticus selectively alters microRNA contents. We also characterized editing sites of the exosome-enriched miRNAs and found six exosome-enriched miRNAs that were Adenosine-to-Inosine (ADAR) edited with the majority of the editing events predicted to occur within microRNA seed regions. However, the prevalence of these editing events was not altered by status epilepticus. These studies demonstrate that status epilepticus alters the exosome pathway and its microRNA content, but not editing patterns. Further functional studies will be needed to determine if these changes have pathophysiological significance for epileptogenesis.